Convectional Influences on The Weather Pattern of Northern Sri Lanka - Nagamuthu, Piratheeparajah; Chan, Ngai Weng (European Publisher, 2019)
There are three precipitation processes, such as monsoon circulation, frontal process, and the convectional process that influence the rainfall of the Northern region of Sri Lanka. Several natural and anthropogenic factors influence the weather pattern of the study area. Even though, recently, convectional influences on the weather pattern are vital. This paper examines the importance of the convectional process in the weather pattern of the Northern Region of Sri Lanka. The main objective of this paper is, to identify the influence of the convectional process in the weather pattern of Northern Sri Lanka. This study uses meteorological data such as rainfall, temperature, relative humidity, and atmospheric pressure. The data were analysed employing the descriptive statistical method using average, standard deviation, and trend analysis via Microsoft Excel worksheet, and results were mapped using Arc Map 11.2 version. Results show that there are significant influences of the convection process in the weather pattern of the study area. Convection contributes more than 38% of the total rainfall, and this is the leading cause of rainfall during the first inter-monsoon season (FIMS) and the southwest monsoon season (SWMS). The Convectional process is also the primary cause for the variations in the temperature range between day and night during March, April, May, June, July, and August. Convection creates an unstable evaporation rate, which leads to the high rates of relative humidity in the nights during the FIMS. Convectional processes contributing to the unstable atmospheric pressure and resulted in unexpected weather disturbance in the study area.